Primary Cesarean Rate at Hospital de Clínicas de Porto Alegre - Ariane Dias Paim (Clinical and Biomedical Research, 2009)
Background: Primary cesarean section is that one performed for the first time in a pregnant woman. It is a more accurate and reliable indicator than the overall cesarean rate, since in women with a previous cesarean section the procedure tend to be repeated. Objectives: To study the primary cesarean section rate at Hospital de Clínicas de Porto Alegre (HCPA) from January 2004 to December 2007 and to observe, preliminarily, the impact of a policy suited for the reduction of primary cesarean-section, implemented in 2006. Patients and Methods: The sample is comprised of 13055 deliveries occurred in the period from January 2004 to December 2007. Demographic features, obstetric history and type of delivery were obtained from medical records of the hospital management System (HCPA IG). Results: A decrease in primary cesarean rate from 2004 to 2007 was evident. The 2007’s rate was beneath the average of the previous 3 years, around 20 to 25% and the highest rate occurred at Tuesdays and the lowest at Saturdays. The rate tended to increase with maternal age, peaking at 40- 44 years. The index was of 25% among SUS patients (public health insurance) against 64% and 66%, respectively among private and other health insurance plan patients. Conclusion: The primary cesarean rate at HCPA decreased since 2004, from 25,72 to 24,34%. Age is a risk factor for primary cesarean section, possibly due to increased obstetrics complications in elderly woman. The implemented policy to lower the primary cesarean rate to approximately 25% accomplished the target.